Improving Student’s Writing Skill of Descriptive Text by Using Instagram Posts as Visual Media - Alfin Candra Adi Pratama; Hartono Hartono (Journal of Advanced Multidisciplinary Research, 2020)
Writing is one amongst the important skills learned in English. In writing, people express their ideas and opinions. In this era of advanced communication technology, the use of social media to teach and assist students to learn is common for educators. This research investigated the effectiveness of using Instragram in teaching writing of descriptive texts.  As pre-experimental research, this research used written tests of descriptive texts as the main instrument and interview as the supplementary data collection technique. The samples of this research were eleventh grade students of Social one of a public senior high school in Semarang. The result of this research showed that there was a significant difference on the students’ ability of writing descriptive texts before and after the treatment. The interview responses also indicated that using Instagram post as visual media for learning descriptive was effective. In conclusion Instagram posts as visual media in teaching descriptive texts can improve student’s writing ability of descriptive text.